A "turn on" fluorescent probe for heparin and its oversulfated chondroitin sulfate contaminant. Issue 11 (3rd August 2015) - Ding, Yubin; Shi, Leilei; Wei, Hui
Abstract : The conjugation of tetraphenylethene and a heparin binding peptide afforded a "turn on" fluorescent probe for reliable determination of heparin and its contaminant oversulfated chondroitin sulfate. Abstract : Designing "turn on" fluorescent probes for heparin (Hep), a widely used anticoagulant in clinics, is of great importance but remains challenging. By introducing a Hep specific binding peptide AG73 to a typical aggregation induced emission (AIE) fluorogen, tetraphenylethene (TPE), a sensitive and selective "turn on" fluorescent probe namedTPE-1 for Hep was developed.TPE-1 was able to detect Hep in a wide pH range of 3–10 without obvious interference from tested anions and biomolecules, especially Hep analogues known as chondroitin sulfate (Chs) and hyaluronic acid (HA). The detection limit of Hep sensing was 3.8 ng mL −1, which was far below the clinically demanded concentration of Hep. The probe was applicable to both unfractionated Hep and low molecular weight Hep, the two main heparin products clinically used. Besides, the fluorescence of Hep boundTPE-1 can be turned off via sequential treatment with heparinases. Importantly, this phenomenon allows us to develop an enzyme assisted strategy for "turn on" sensing of oversulfated chondroitin sulfate (OSCS) with a detection limit of 0.001% (w%), which is the main contaminant in Hep and may cause severe adverse reactions including death.